2017
DOI: 10.1002/sia.6278
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of plasma‐treated carbon fiber reinforced PTFE composites with CNT

Abstract: This paper is concerned with the effects of the plasma surface treatment and the addition of CNT on the mechanical properties of carbon fiber/polytetrafluoroethylene (PTFE) composite. The tensile and flexural strength of composites containing CNT and plasma‐treated carbon fibers improved. The flexural strength first decreases with respect to the CF content. The flexural strength increases to 179 MPa for the plasma‐treated composite as compared with 167 MPa for the neat carbon fiber composites. The overall impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Therefore, in order to increase the wear resistance of PTFE-based composites filled with fibers, dispersed fillers (oxides, layered silicates, sulfides, and graphite) are additionally added into them [ 18 , 19 , 20 , 21 ]. In the work of Ronghao L. et al [ 22 ] investigated the effect of plasma-treated CNTs on the mechanical properties of PTFE/CF composites. It is shown that the introduction of combined fillers into PTFE leads to an overall improvement in mechanical properties by 8% relative to composites with a monomodifier.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to increase the wear resistance of PTFE-based composites filled with fibers, dispersed fillers (oxides, layered silicates, sulfides, and graphite) are additionally added into them [ 18 , 19 , 20 , 21 ]. In the work of Ronghao L. et al [ 22 ] investigated the effect of plasma-treated CNTs on the mechanical properties of PTFE/CF composites. It is shown that the introduction of combined fillers into PTFE leads to an overall improvement in mechanical properties by 8% relative to composites with a monomodifier.…”
Section: Introductionmentioning
confidence: 99%